Between compassion and conservatism: a genealogy of British humanitarian sensibilities - Pupavac, Vanessa (Zone Books, 2010)
Abstract: The chapter explores continuities in modern British humanitarianism at its birth two hundred years ago and today. Modern British humanitarianism arose out of the contradictions between humanist ideals, expanding social sympathies, and fears of radical political change following the French Revolution. Its development was strongly influenced by middle class evangelical reform circles, exemplified by the abolitionist William Wilberforce. The chapter argues that British humanitarianism today follows Wilberforce’s conservative humanitarian tradition and his anti-progressive views. A final proofed version of this paper was published as a chapter:- Vanessa Pupavac (2010) ‘Between Compassion and Conservatism: A Genealogy of British Humanitarian Sensibilities’, in Didier Fassin and Mariella Pandolfi (eds) States of Emergency: Anthropology of Military and Humanitarian Intervention. New York: Zone Books (distributed by MIT Press), pp. 47-77.